Generation of transgene-free porcine intermediate type induced pluripotent stem cells. Issue 23 (2nd December 2018) - Li, Dong; Secher, Jan; Hyttel, Poul; Ivask, Marilin; Kolko, Miriam; Hall, Vanessa Jane; Freude, Kristine K
ABSTRACT: Physiologically and anatomically, humans and pigs share many similarities, which make porcine induced pluripotent stem cells (piPSCs) very attractive for modeling human cell therapy as well as for testing safety of iPSC based cell replacement therapies. To date, several integrative and non-integrative strategies have been reported to successfully generate piPSCs, but all resulting piPSCs had integration of transgenes. The use of integrative methods has the disadvantage of potential lack of silencing or inappropriate re-activation of these genes during differentiation, as well as uncertainty regarding disruption of important genomic regions caused by integration. In our study, we performed a non-integrative vector based reprogramming approach using porcine fetal fibroblasts. The resulting four piPSC lines were positive for pluripotency marker and when subjected to in vitro and in vivo differentiation assays, all four lines formed embryoid bodies, capable to differentiate into all three germ layers, and three out of the four cell lines formed teratomas. PCR analysis on genomic and plasmid DNA revealed that the episomal vectors were undetectable in six out of eight subclones derived from one of the piPSC lines (piPSC1) above passage 20. These piPSCs could potentially be ideal cell lines for the generation of porcine in vitro and in vivo models. Furthermore, subsequent analyses of our new transgene independent piPSCs could provide novel insights on the genetic and epigenetic necessities to achieve and maintain piPSCs.